KEPEMIMPINAN ISLAM BERWAWASAN DUNIAWI DAN UKHRAWI - Hamdani Khairul Fikri (Universitas Islam Negeri (UIN) Mataram, 2015)
Leadership is a process to influence other people and effort to call people to do goodness and forbid people to do badness. In Islamic context, leadership is realization of faithand good deeds. Leadership also cannot be separated from a leader because a leader is an expert in social organization who is expected to use his/her influence in doing vision and mission of an organization. Finding of this paper is that the figure of the most ideal leader in this world is the messenger (Rasullullah) SAW because he always started to lead himself, to lead his words so he never spoke anything but the truth, beautiful words, and full of meaning. The messenger also leaded his lust, desire, family withthe best way because the messenger always adhered to the rules which were established by Allah SWT so he could lead the community in the best way. In Islam it has been set criteria for a leader, such as: faith, good deeds, having sincere intention, male, do not ask position, adhering to the law of Allah, judge justly, advisingthe people, do not accept gifts, having firm and gentle character,and also having STAF characters (truth, delivering messages/sermon, mandate, and wise). The leader also should has balances between worlds and hereafter based on the criteria mentioned aboveas criteria of leader based on al-Qur’an and as-Sunnah and also asleadership type with a wide perspective about the world and hereafter.